Prevalence of Recto-Vaginal Colonization of Group B Streptococcus in Pregnant Women - Moloud Absalan; Gilda Eslami; Hengameh Zandi; Ahmad Mosaddegh; Mahmood Vakili; Mohammad Bagher Khalili (مجله دانشکده پزشکی اصفهان, 2013)
Background: Streptococcus agalactiae is the major cause of meningitides and septicemia in infants and also intrauterine infection and preterm labor in pregnant women. This study aimed to determine the prevalence of group B streptococci (GBS) colonization in rectovaginal region of 15 to 40 years, pregnant women.